(untitled) (Journal of Computational Mathematics, 2021)
In this paper, a class of non-linear methods proposed in [1] is discussed. A new derivation of the methods is given. The analysis based on the new derivation shows that this class of methods is not suitable for stiff problems. The numerical tests support our argument.